Haze Pollution in the Unstable Atmospheric Boundary Layer Over the West Bank of Taiwan Strait Induced by Regional Transport of PM2.5. Issue 10 (30th September 2022) - Jiang, Y. C.; Zhao, T. L.; Tan, C. H.; Li, F.; Zheng, Q. P.; Shu, Z. Z.; Ma, X. D.; Zheng, H.; Lv, Q. Y.
Abstract: This study investigated the regional transport of particulate matter (PM2.5 ) leading to air pollution in Fuzhou, in the west bank of the Taiwan Strait (WBTS), which has a relatively good air quality with a lower aerosol optical depth than that of East China. The continental polluted aerosol zone over the coast of East China was identified as an aerosol transport belt, and the daily aerosol dynamics observed by MODIS remote sensing indicated the southward transport of fine particulate matter to the WBTS along the coast. The external air pollutants from regional transport contributed 84% of the PM2.5 detected in Fuzhou, while only 16% due to local emissions of air pollutants. The northerly winds of the cold front drove the southward transport of polluted air masses along the coast of the northwest Pacific from the Yangtze River Delta (YRD) to the WBTS. The vertical mixing of air pollutants from the upper boundary layer to the surface layer could be conducive to regional‐transport‐induced haze pollution in this coastal area of the WBTS. Fuzhou is considered a receptor region of PM2.5 transport in Eastern China, and the source region is mainly from the YRD. The results of this study have significant implications on determining the source of pollution and controlling local air quality for good air quality regions. This study also shed some light on using multi‐satellites to fill the surface observation gaps in coast or nearshore areas, and to confirm the characteristics and passways of aerosol transport. Key Points: The southward transport of air pollutants built up a source‐receptor relationship in East Aisa Monsoon region The transport of exogenous PM2.5 accounts for more than 80% during a severe haze pollution in Fuzhou The unstable atmospheric boundary layer leads to the downward mixing of PM2.5 to the surface in clean areas